(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Tourism in the Republic of Uzbekistan is one of the priorities of the economy, the development of which contributes to the creation of new jobs, the growth of entrepreneurial and investment activity, the development of service and hospitality infrastructure, cleanliness of the environment, living standards and international cooperation.